Pengaruh Store Atmosphere, Etika Bisnis dan Kualitas Produk Terhadap Kepuasan Konsumen - Dahmiri Dahmiri; Sylvia Kartika Wulan Bhayangkari (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study aims to analyze the influence of the influence of store atmosphere, business ethics and product quality on consumer satisfaction at the syariah syariah mini market 212 Jambi branch. Survey research using a questionnaire instrument, a sample of 70 respondents with nonprobability sampling techniques. Data analysis uses multiple linear regression. The results of the study concluded that the characteristics of respondents were dominated by women, aged 20 to 29 years, the last education occupations were dominated by students. Simultaneously store atmosphere, business ethics and product quality have a positive and significant effect on customer satisfaction, so also partially store atmosphere variables, business ethics and product quality have a positive and significant effect on customer satisfaction.